Spirituality and Ethics in Management
XII, 222 p.
Keywords: The signi? cance of “spirituality in management” is acquiring considerable international recognition. It is one of the “hottest” emerging ? elds in management. A number of recent events underscore this development. In February 2000 the Indian Institute of Management organized a “Corporate Reputation for Competitive Advantage” workshop in Calcutta, which focused on spirituality, ethics and leadership. The conference “Business, Religion and Spirituality” was held at the University of Notre Dame in April th 2000. In April 2001 the International Academy of Business Disciplines held its 13 annual meeting in Orlando, Florida and had a track on Spirituality in Organizations. In April 2002 a world conference was organized in New York entitled “Spirit in Business: Ethics, Mindfulness and the Bottom Line. ” These and other important scienti? c events clearly show that spirituality is no longer considered to be purely a matter of individual search, and is becoming more and more recognized in management and business ethics circles. Our “Spirituality in Management” workshop was held in July 1–3, 2001 in Szeged, Hungary. It was jointly organized by the Business Ethics Center of the Budapest University of Economic Sciences, the Faculty of Economics and Business Administration and the Department for the Study of Religion of the University of Szeged. Scholars and practitioners from 13 countries represented disciplines as diverse as economics, business, management studies, philosophy, theology, sociology, and medical anthropology. Participants included PETER PRUZAN, Copenhagen Business School (Denmark); S. K.